PRINSIP KERJASAMA DAN MUSYAWARAH DALAM RUMAH TANGGA (PERSPEKTIF ALQURAN SURAH AN-NISA AYAT 35) - Syarifudin; Madaniah (STAI DI AL-HIKMAH, 2024)
Issues between husbands and wives in a household are a common occurrence, whether they are minor or major. However, Islam teaches that these issues should be resolved in a better manner, namely through the method of deliberation and the principle of cooperation. In the Qur'an, Allah SWT provides the best guidelines for resolving conflicts in the household, as found in Surah An-Nisa, verse 35. This verse emphasizes the importance of a fair and wise mediator in resolving disputes between husbands and wives, ensuring that the issue is addressed in the right way, benefiting both parties. If the couple applies this method, they will find a better and more insightful way to handle various challenges in their marriage. This paper aims to examine the interpretation of Surah An-Nisa, verse 35, and understand the implications of the principle of deliberation in married life. By using both classical and contemporary exegesis approaches, this paper will explain how the principle of deliberation can not only be a solution to marital conflicts but also foster a more harmonious and blessed life. A good understanding of this verse is expected to serve as a guideline in building a strong family based on Islamic values.